Rare Lipomatous Tumor of the Posterior Mediastinum in Children - Takahiro Homma; Yoshinori Doki; Kazutaka Senda; Masayoshi Toge; Yutaka Yamamoto; Toshihiro Ojima; Yoshifumi Shimada; Naoki Yoshimura (Georg Thieme Verlag KG, 2014)
Abstract The mediastinum is a unique anatomic area containing various structures and pluripotent cells, which allow for the development of a range of tumors. We report two pediatric cases of a lipomatous tumor of the posterior mediastinum. Complete surgical excision of the mass in each was achieved through a lateral thoracotomy. Histopathologic findings showed a lipoma in one case and a lipoblastoma in the other. A lipomatous tumor in the posterior mediastinum is extremely rare and preoperative diagnosis is difficult. When an operative plan is being considered, the presence of a potentially malignant tumor should be kept in mind.